2018
DOI: 10.3390/ma11091758
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Purification of Aucubin from Eucommia ulmoides Ionic Liquid Extract Using Macroporous Resins

Abstract: Aiming to address the shortcomings of high-concentration ethanol or methanol extraction solutions that need to be diluted and concentrated prior to use in conventional macroporous resin adsorption approaches, an efficient approach for enrichment and purification of aucubin from the ionic liquid extraction solution of samaras of Eucommia ulmoides was proposed. Among the nine kinds of macroporous resins investigated, the HPD850 resin was found to be the most suitable. Equilibrium adsorption tests were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The global HPLE-RP condition, 15%, 150 °C and 80%, allowed the highest recovery of phenolic acids, with gallic acid being the most abundant (~70%) (Table 4). Yang et al [62] observed a similar behavior during RP, arguing that probably the compounds of interest are more stabilized by the interactions with the solvent than by the interactions with the resin surface. Hence, the higher the ethanol content in the raw extracts, the lower the polyphenols content in the purified extracts (Table 4).…”
Section: Resultsmentioning
confidence: 89%
“…The global HPLE-RP condition, 15%, 150 °C and 80%, allowed the highest recovery of phenolic acids, with gallic acid being the most abundant (~70%) (Table 4). Yang et al [62] observed a similar behavior during RP, arguing that probably the compounds of interest are more stabilized by the interactions with the solvent than by the interactions with the resin surface. Hence, the higher the ethanol content in the raw extracts, the lower the polyphenols content in the purified extracts (Table 4).…”
Section: Resultsmentioning
confidence: 89%
“…In order to fully recover aucubin, it is necessary to select a suitable desorbent that can dissolve the resin-enriched aucubin as much as possible in a small volume of desorbent. Under the same conditions, the solubility of aucubin in ethanol is higher than that in water . Besides, ethanol can be recycled and reused.…”
Section: Resultsmentioning
confidence: 99%
“…Under the same conditions, the solubility of aucubin in ethanol is higher than that in water. 53 Besides, ethanol can be recycled and reused. On the basis of this, ethanol was selected as the desorbent in the desorption test.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…It is reported that chlorogenic acid can protect mice against Cd-induced hepatorenal injury via regulating intestinal flora balance ( Ding et al, 2021 ). Except chlorogenic acid, geniposidic acid and aucubin are the other characteristic components with high contents in E. ulmoides ( Wang et al, 2016 ; Yang et al, 2018 ). Based on the rich foundation of natural products, E. ulmoides possess multiple pharmacological activities, such as anti-inflammatory and antihyperlipidemia ( Wang et al, 2019 ; Gu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%